Study on Mamuju clear water supply infrastructures - Abdi Manaf (Indonesia Prime, 2018)
The study Is dedicated to describe the condition of water supply infrastructure in Mamuju and to investigate the fresh water supplied to the domestic customers, viewed from its quality, quantity, and continuity by Manakarra, Mamuju Regional Water Supply Company (PDAM), projecting requirement of five years later, then (the year 2006-2011) The relevant data collected through observations on the water quality. The data are analyzed and described qualitatively using inferential statistics. The result proves that the quantity, ad continuity variables have a significant influence on the availability of water supply infrastructure of Manakarra. The strongest influence comes from the quantity factor, and the continuity and quality respectively. The availability of standard water is important to increase the quantity, continuity of water supply and to improve the performance of the company in fulfilling the quality standard of water to the customers. The intake capacity in 2011 is 196,25 litre/second to meet the water demand of 37,95 litre/second.